Investigation of single and double action mechanical deflection - Heap, Yee Nean; Usubamatov, Ryspek, Prof. Dr. (Malaysian Technical Universities Network (MTUN), 2011)
Malaysian Technical Universities Conference and Exhibition on Engineering and Technology (MUCEET 2009) organized by Malaysian Technical Universities Network (MTUN), 20th - 22nd June 2009 at M.S. Garden Hotel, Kuantan, Pahang.